CULTURAL AND CIVILIZATION ORIGINS OF FORMING POLITICAL AS A SOCIAL PHENOMENON - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
On the basis of the socio-philosophical research of the phenomenon of political the basic cultural and civilization factors of its development are determined and the concept of the political is being output.